THE IMPACT OF LOCAL POTENTIAL-BASED COMMUNITY EMPOWERMENT THROUGH THE TOURISM VILLAGE PROGRAM IN CIKOLELET VILLAGE, CINANGKA DISTRICT, SERANG-BANTEN REGENCY - Risdawati, Risdawati; Hermansah, Tantan (Universitas Islam Negeri Raden Intan Lampung, 2022)
There are several ways to empower rural communities, one of which is through tourism. The community can benefit from their expertise in managing natural resources, such as processing coffee beans into ground coffee, which will become the village's trademark. The Cikolelet Tourism Village, located in Cinangka District, Serang Regency, Banten, is expected to alleviate poverty by reducing unemployment, inequity, and job creation. Furthermore, it has the potential to benefit coffee farmers and the surrounding community. The purpose of this study is to describe the Cikolelet Village Government's contribution to the local potential-based tourism village program and to analyze the impact of the tourism village program. The qualitative approach was used in this study, with data obtained through observation, interviews, and documentation studies. The research data sources are primary and secondary data sources, and the data analysis techniques are those proposed by Miles and Huberman. The study's findings indicate that the tourism village program needs to be implemented optimally. However, the tourism-supporting sector, specifically coffee production under the Cikopi brand, has achieved independence and is no longer dependent on the tourism village program. The community felt the impact of the public awareness always to protect the environment and capitalize on the local potential. Income is increasing, coffee productivity is rising, and the community can contribute adequately.